SOLUTIONS FOR USING PATTERNS IN MODERN BUILDING ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
Patterns play a significant role in modern architecture, enhancing aesthetics, functionality, and sustainability. From decorative façades to energy-efficient structures, patterns contribute to both design and performance. This article explores various solutions for integrating patterns into contemporary buildings effectively.